The anterior component of occlusal force revisited: direct measurement and theoretical considerations. - Al Qassar, Sarmad S Salih; Mavragani, Maria; Psarras, Vasilis; Halazonetis, Demetrios J (Eur J Orthod, 2016)
BACKGROUND: The anterior component of occlusal force (ACF), considered to result from the mesial inclination of teeth relative to the occlusal plane, has been estimated by indirectly measuring contact point tightness (CPT) through interproximal insertion of metal strips. ACF has been observed concurrently with a posterior component, whose theoretical origin is difficult to explain. OBJECTIVES: Evaluate ACF by measuring CPT directly, and integrate current data to propose a theoretical basis for ACF. MATERIALS AND METHODS: The sample comprised 14 females (age: 22.3±2.8) and 16 males (age: 20.8±2.5). Our device consisted of two force sensors: one for measuring maximum bite force (MBF) (overall thickness: 4mm), and one for measuring CPT directly (0.2mm thick), inserted between the lower first molar and second premolar. ACF was computed as the difference in CPT between the biting (at 75 per cent of MBF) and non-biting conditions. RESULTS: Averages of MBF, CPT, and ACF were 666.67 [standard deviation (SD): 36.06], 6.74 (SD: 1.17), and 20.59 (SD: 4.60) N, respectively. ACF, CPT, and MBF were higher in males by approximately 28, 18 and 7 per cent, respectively. A positive correlation was observed between ACF and MBF (R (2): 0.64). CPT was also significantly correlated to MBF (R (2): 0.40). Biomechanical analysis indicates that previously offered explanations do not unriddle the concurrent increase of CPT at anterior and posterior contact points. CONCLUSIONS: ACF was related to bite force by a logarithmic model. We speculate that CPT increases during biting through a combination of mesial tipping of teeth and mandibular bending.
Keywords: Adolescent; Adult; Bicuspid; Biomechanical Phenomena; Bite Force; Cuspid; Dental Occlusion; Female; Humans; Incisor; Linear Models; Male; Mandible; Models, Biological; Molar; Sex Factors; Signal Processing, Computer-Assisted; Tooth; Transducers; Young Adult